2020
DOI: 10.4330/wjc.v12.i10.475
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarettes — myocardial infarction, hemodynamic compromise during pregnancy, and systolic and diastolic dysfunction: Minireview

Abstract: The aim of this study was to review the most recent literature on the safety of electronic cigarettes (ECs) in the context of cardiovascular disease and in the context as a tool for smoking cessation and recreational purposes. The format of this review begins with relevant research from the basic sciences and follows through with a pertinent review of clinical trials. Daily use of ECs has implications in myocardial infarction (MI) with an odds ratio of 1.70 compared to healthy, nonsmokers and even worse risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Worth reporting is a significant risk related to e-smoking-induced endothelial and platelet dysfunction observed in rat models. In conclusion, it is not possible to support the use of e-cigarettes as a safe alternative to tobacco smoking discontinuation also in the scenario of cardiovascular diseases (Vajdi and Tuktamyshov, 2020).…”
Section: Clinical Impact Of E-cigarettes and Vapingmentioning
confidence: 97%
See 2 more Smart Citations
“…Worth reporting is a significant risk related to e-smoking-induced endothelial and platelet dysfunction observed in rat models. In conclusion, it is not possible to support the use of e-cigarettes as a safe alternative to tobacco smoking discontinuation also in the scenario of cardiovascular diseases (Vajdi and Tuktamyshov, 2020).…”
Section: Clinical Impact Of E-cigarettes and Vapingmentioning
confidence: 97%
“…It has been widely demonstrated that vaping and e-smoking remain a threat to cardiovascular health (Vajdi and Tuktamyshov, 2020; Marques et al ., 2021). Although a minority of studies support e-smoking as a less dangerous alternative to tobacco cigarettes for cardiovascular health, the vast majority of published papers report some level of harm, with regard to free radical generation, diastolic functional modifications, development of atherosclerosis and incidence of myocardial infarction, in particular when focusing on long-term use.…”
Section: Clinical Impact Of E-cigarettes and Vapingmentioning
confidence: 99%
See 1 more Smart Citation